Euro area fiscal stance - Krzysztof Bańkowski; Marien Ferdinandusse (European Central Bank (ECB), 2017)
This paper analyses the appropriateness of the euro area fiscal stance. In this context, the paper presents the relevant definitions and how the euro area fiscal stance has evolved over time. Furthermore, it contains an evaluation of the appropriateness of the euro area aggregated fiscal stance set out in the European Commission's Spring 2016 European Economic Forecast, concluding that, while it is broadly appropriate from the stabilisation perspective, it deviates slightly from the sustainability objective. Finally, the paper investigates the impact of a fiscal stimulus in Germany on the main euro area macroeconomic variables under an adverse risk scenario. The analytical exercise conducted in the paper is agnostic about the relative weights of the stabilisation and sustainability objectives and considers them separately. This is distinct from the SGP framework, which synthesises the two, placing a stronger emphasis on the latter. The ultimate aim of this approach is to analyse the possible interactions between the two objectives at the current juncture.
Keywords: E61; 330; debt sustainability; fiscal stance; output gap; output stabilisation